1982
DOI: 10.1002/jsfa.2740330815
|View full text |Cite
|
Sign up to set email alerts
|

Determination of organic acids and sugars in guava (Psidium guajava L.) cultivars by high‐performance liquid chromatography

Abstract: The major organic acids and sugars in five Florida guava cultivars were analysed by high-performance liquid chromatography. Glycolic, malic, ascorbic and citric acids were determined, citric being the major acid in all five cultivars. Ascorbic acid levels varied more than ten-fold (0.04-0.44%) among the cultivars. Trace amounts of fumaric acid were detected for the first time in guava fruit. In all cultivars, fructose was the major sugar; glucose and sucrose were also determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
6

Year Published

1989
1989
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 6 publications
1
22
0
6
Order By: Relevance
“…A acidez em produtos hortícolas é atribuída, principalmente, aos ácidos orgânicos que se encontram dissolvidos nos vacúolos das células, tanto na forma livre, como combinados com sais, ésteres, glicosídeos, etc. Em goiabas, o principal responsá-vel pela acidez é o ácido cítrico (Wilson et al, 1982). O aumento da acidez titulável pode ser explicado, em parte, pelo aumento no teor de ácido ascórbico, o qual também foi verificado em todos os tratamentos.…”
Section: Resultsunclassified
“…A acidez em produtos hortícolas é atribuída, principalmente, aos ácidos orgânicos que se encontram dissolvidos nos vacúolos das células, tanto na forma livre, como combinados com sais, ésteres, glicosídeos, etc. Em goiabas, o principal responsá-vel pela acidez é o ácido cítrico (Wilson et al, 1982). O aumento da acidez titulável pode ser explicado, em parte, pelo aumento no teor de ácido ascórbico, o qual também foi verificado em todos os tratamentos.…”
Section: Resultsunclassified
“…Similar results were found by Mowlah and Itoo (1983), ascorbic acid content in the two cultivars examined increasing throughout maturation, ripening and storage, reaching over 270 mg.l00g-1 in both cultivars. Itoo et al (1980) reported that guava fruits have ten times more ascorbic acid than oranges; however, ascorbic acid levels have been shown to vary from 0.04% to 0.44% depending upon the cultivar (Wilson et al, 1982a).…”
Section: Compositionmentioning
confidence: 98%
“…Fructose is the major sugar present in the ripe fruits of both Florida (Wilson et al, 1982a) and Vietnamese type cultivars (Salmah and Mohamed, 1987). Fructose comprises 55.93% and 52.85% of the sugar in white and pink cultivars respectively (Mowlah and Itoo, 1982).…”
Section: Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a good source of ascorbic acid, sugars, pectinand some minerals. Its flesh and skin colours vary from variety to variety depending on the pigment type and the amount [1]. Tropical Fruit juices have turn out to be important in recent years due to the overall increase in natural fruit juice consumptions as an alternative to the conventional caffeine-containing beverages such as coffee, tea or carbonated soft drink [2].…”
Section: Introductionmentioning
confidence: 99%